O general judeu e o cidadão romano: o discurso de construção de Flávio Josefo em Vita (Século I d.C.) - Oliveira, Bruno Pegorari (2016)
This master’s degree dissertation intends to analyze and discuss the Flavius Josephus’s construction speech (37-100 a.C.) by his work Vita. Throughout this study, we will present the historical context of Palestine, focusing in the Roman domination, development of Herods’s government, and the successive foreign achievements in the first century a.C., we will observe some questions related to Josephus’s origin and rise, as well his participation during the war between jews and romans (66-70 a.C.). Lastly, we will analyze the Jewish historian’s speech in Vita, observing his positioning throughout the work. This study is based on bibliographic research (historiography) concerning on the subject, as well the document analysis (sources) produced by this historian at the end of the first century of Christian era.